Messaging and national park visitor attitudes - Taff, Brendan Derrick, author; Newman, Peter, advisor; Bright, Alan, committee member; Timpson, William, committee member; Vagias, Wade, committee member (Colorado State University. Libraries, 2012)
National Park Service annual visitation is approaching 300 million, and managers must balance internal stress, such as visitor use, and external stress, such as noise from aircraft overflights, while protecting resource and social conditions. Attitudes affect visitor perceptions of these influences, and largely determine behaviors via behavioral intentions. The purpose of this dissertation is to evaluate national park visitor attitudes, specifically in regard to Leave No Trace minimum impact practices, alternative transportation, and soundscapes, and to increase understanding of effective strategies, such as educational messaging, which can alter visitor attitudes, perceptions and behaviors. This dissertation summarizes three studies and is presented as three journal articles suitable for submission to tier one or two journals. It begins by describing the origins of visitor capacity in national parks, and the associated frameworks and theoretical models that assess visitor perceptions and assist with the creation of effective messaging. The Theory of Planned Behavior and the Elaboration Likelihood Model are introduced as pertinent frameworks to the development of effective messaging which can alter visitor attitudes and perceptions. Chapters two and three present studies which evaluated visitor attitudes in NPS units, and chapter four builds upon this understanding by testing theoretically-based messaging with park visitors to determine if messaging can alter perceptions. Chapter five connects these studies by discussing how messaging can be applied in parks to alter visitor attitudes, perceptions and behaviors, while suggesting implications of the results and recommendations for future research. Study one investigates day-user and backcountry-overnight visitor attitudes concerning Leave No Trace at Rocky Mountain and Olympic National Parks. Leave No Trace is the most prominent educational message used to influence behaviors of protected-areas visitors with the end-goal of sustaining or improving resource conditions. The majority of previous research regarding Leave No Trace has focused on backcountry-overnight visitors. However, day-users are by far the largest user group of protected areas, and yet, research focused on this large and growing segment of users has been neglected. The purpose of this study was to enhance understanding of day-user knowledge, awareness and perceptions, and attitudes regarding Leave No Trace and compare them with those of overnight users. Greater understanding of the similarities and differences between these two user-groups is essential so that management can improve efficacy and create effective messaging strategies that alter behaviors and curb depreciative actions. Study two examines visitor attitudes toward alternative transportation systems in Rocky Mountain and Yosemite National Parks. The National Park Service is increasingly using alternative transportation to accommodate escalating visitation, while reducing the reliance upon personal vehicles that have attributed to resource and social condition impacts. Understanding of visitor perceptions of alternative transportation is vital for managers so that they may develop effective management strategies, frameworks, and messaging concerning alternative transportation use, yet little is known about visitor attitudes toward these systems. The purpose of this study was to examine visitor attitudes toward the alternative transportation experience and to determine salient variables that can be applied to user capacity frameworks, communication strategies, and park planning. Study three explores the role of educational messaging on visitor perceptions of military aircraft sounds in Sequoia National Park. Mandates require that the National Park Service protect natural soundscape, and research suggests that opportunities to experience natural sounds are among the most important reasons for visiting parks. Aircraft overflights are a significant source of anthropogenic noise intrusion in parks, and studies suggest that visitors frequently find these events annoying and unacceptable. The National Park Service must integrate methods to mitigate these impacts, and the purpose of this study was to evaluate the role of educational messaging and to determine if this information can significantly affect visitor acceptability of military aircraft sounds by altering visitor expectations.
Keywords: attitudes; education; messaging; parks; recreation; visitors